Ultrahigh Detectivity Broad Spectrum UV Photodetector with Rapid Response Speed Based on p‐β Ga2O3/n‐GaN Heterojunction Fabricated by a Reversed Substitution Doping Method. Issue 16 (22nd January 2023) - Han, Yurui; Wang, Yuefei; Fu, Shihao; Ma, Jiangang; Xu, Haiyang; Li, Bingsheng; Liu, Yichun
Abstract: An excellent broad‐spectrum (220–380 nm) UV photodetector, covering the UVA‐UVC wavelength range, with an ultrahigh detectivity of ≈10 15 cm Hz 1/2 W −1, is reported. It is based on a p‐β Ga2 O3 /n‐GaN heterojunction, in which p‐β Ga2 O3 is synthesized by thermal oxidation of GaN and a heterostructure is constructed with the bottom n‐GaN. XRD shows the oxide layer is (−201) preferred oriented β‐phase Ga2 O3 films. SIMS and XPS indicate that the residual N atoms as dopants remain in β Ga2 O3 . XPS also demonstrates that the Fermi level is 0.2 eV lower than the central level of the band gap, indicating that the dominant carriers are holes and the β Ga2 O3 is p‐type conductive. Under a bias of −5 V, the photoresponsivity is 56 and 22 A W −1 for 255 and 360 nm, respectively. Correspondingly, the detectivities reach an ultrahigh value of 2.7 × 10 15 cm Hz 1/2 W −1 (255 nm) and 1.1 × 10 15 cm Hz 1/2 W −1 (360 nm). The high performance of this UV photodetector is attributed mainly to the continuous conduction band of the p‐β Ga2 O3 /n‐GaN heterojunction without a potential energy barrier, which is more helpful for photogenerated electron transport from the space charge region to the n‐type GaN layer. Abstract : The p‐βGa2 O3 /n‐GaN heterojunction is constructed, which shows an ultrahigh detectivity in a wide UV spectrum. The p‐βGa2 O3 is realized by a reversed substitution doping process. The high performance of photodetector is attributed to the continuous conduction band in the heterojunction without a potential barrier, which is helpful for photogenerated electron transport from the space charge region to the n‐GaN layer.